The symmetry of the left and right tibial plateau: a comparison of 200 tibial plateaus - van der Gaast, Nynke; Dunning, Hans; Huitema, Jellina M.; Waters, Andrew; Jaarsma, Ruurd L.; Doornberg, Job N.; Edwards, Michael J. R.; van de Groes, Sebastiaan A. W.; Hermans, Erik (European journal of trauma and emergency surgery (Munich : 2007), 2023)
Purpose This study aims to investigate the symmetry of the left and right tibial plateau in young healthy individuals to determine whether left–right mirroring can be reliably used to optimize preoperative 3D virtual planning for patients with tibial plateau fractures. Methods One hundred healthy subjects, without previous knee surgery, severe knee trauma, or signs of osteoarthritis were included for a previous dynamic imaging study of the knee. The subjects underwent a CT scan, scanning the left and right knee with a slice thickness of 0.8 mm. 3D surface models of the femur, patella, and tibia were created using a convolutional neural network. The 3D models of the left and right tibias were exported to MATLAB © and the tibias were mirrored. The mirrored tibias were superimposed on the contralateral tibia using a coherent point drift surface matching algorithm. Correspondence points on both surfaces were established, the mean root squared distance was calculated and visualized in a boxplot and heatmaps. Results The overall mean difference between correspondence points on the left and right tibial plateau is 0.6276 ± 0.0343 mm. The greatest differences between correspondence points were seen around two specific surfaces on the outside of the tibial plateau; where the distal tibia was cut 15 mm below the tibial plateau and around the tibiofibular joint. Conclusions The differences between the left and right tibial plateau are small and therefore, we can be confident that the mirrored contralateral, unfractured, tibial plateau can be used as a template for 3D virtual preoperative planning for young patients without previous damage to the knee.